Male’s influence on the primary sex ratio bias in Ryukyu drywood termite - Agarie, Ayaka; Miyaguni, Yasushi; Sugio, Koji; Tsuji, Kazuki; Kobayashi, Kazuya (Frontiers in Ecology and Evolution, 2023)
Selfish genetic elements (SGEs) increase their transmission efficiency relative to the rest of the individual genome, which is often deleterious to individual fitness. Theoretical studies have suggested that intragenomic conflict over the sex ratio distortion between SGEs and the rest of the genome should lead to the evolution of sex-determining systems. However, in insects, there are relatively few studies other than those on Dipterans, which makes it difficult to understand the role of SGEs in the evolution of insect sex determination. This is partially due to the difficulties in observing SGEs under field conditions. The effect of SGEs is often masked by the counter-evolution of the resistance genes. Interpopulation cross-breeding experiments are effective to detect the SGEs and their resistance genes. If these populations have different SGEs and resistance genes, cross-breeding experiments reveal their existence by collapsing the evolutionary antagonistic state. The Ryukyu drywood termites Neotermes sugioi, distributed in the Ryukyu Islands, show male-biased sex ratios in pseudergates, nymphs, alates and soldiers both in Okinawa and Ishigaki Islands, but different degrees of bias have been reported between the islands. Male-specific microsatellite alleles have been reported in this species, which allowed us to identify the sex of the eggs and young larvae. In this study, we used the microsatellite locus with male-specific alleles to investigate the primary sex ratio of field colonies on Okinawa and Ishigaki islands and the sex ratio of offspring obtained through cross-breeding experiments between the islands. The primary sex ratios of field colonies were male-biased in Okinawa but not in Ishigaki. Cross-breeding experiments showed that Okinawa males tend to have a male-biased sex ratio in their offspring, but Ishigaki males do not. This result is consistent with the hypothesis that the male bias in this species is caused by SGEs, even though termites are phylogenetically distant from Diptera. Accumulation of knowledge on genetic conflicts in a wide range of taxa might be an important step toward elucidating the mechanisms of diversification of sex determination systems in insects.